Parenting Practices and Adolescent Effortful Control: MAOA T941G Gene Polymorphism as a Moderator - Zhao, Bao; Cao, Yanmiao; Zhang, Liang; Zhang, Wenxin (Frontiers in Psychology, 2020)
Effortful control plays a crucial role in psychopathology disorders. Emerging studies have paid attention to the effects of G×E interaction on effortful control. The present study investigated interactions between monoamine oxidase A (MAOA) T941G polymorphism with parenting practices on effortful control in a sample of 1,331 Chinese adolescents. The adolescents completed the Early Adolescent Temperament Questionnaire–Revised Effortful Control scale and the Parenting Style Index provided during the study to assess effortful control and parenting practices, respectively. MAOA T941G polymorphism exerted no effect on adolescent effortful control; however, results revealed that the MAOA gene interacted with parental acceptance/involvement in their associations with effortful control among boys. Specifically, although increased levels of parental acceptance/involvement benefited all adolescents, boys with G alleles of the MAOA gene exhibited higher sensitivity to parental acceptance/involvement, compared with T carriers; this interaction was not significant among girls. This study is the first to identify MAOA × parenting interaction on adolescent effortful control, further contributing to the literature in MAOA gene–effortful control.